Weyl Semimetal-Based Terahertz Chips for the Determination of Nickel Metal Particle Concentration in Sewage - Chao Lin; Hao Xu; Yang Ping (Photonics)
A novel terahertz-responsive chip was developed for rapid, non-contact detection of nickel metal particle concentrations in aqueous solutions. The chip integrates a Weyl semimetal thin film as the active layer and a sub-wavelength metallic structure as the substrate. Upon terahertz wave irradiation, distinct responses were observed in liquids containing varying nickel concentrations, enabling the establishment of a robust correlation between concentration and terahertz signal. Experimental results demonstrate the chip’s capability to quantify nickel particles (10–30 μm), with a detection limit below 0.01 mg/L and a relative standard deviation of <3% across repeatability tests. This technology offers a high-speed, precise, and low-limit solution for water quality monitoring, with significant potential for environmental applications.